Perancangan UI/UX Prototype Pelaporan Pembelajaran Siswa Menggunakan Metode Design Thinking Berbasis Website di MAN Lhokseumawe - Syahru, Muhammad; Ilham, Muhammad (Decode: Jurnal Pendidikan Teknologi Informasi, 2026)
Advances in educational information systems have driven the use of digital platforms in educational administration, including web-based student grading systems. However, suboptimal system design in terms of interface and navigation continues to pose challenges for users in the grading process. This study aims to design a prototype user interface (UI) and user experience (UX) for a web-based learning reporting system at MAN Lhokseumawe using the design thinking method. The research was conducted through the stages of empathise, define, ideate, prototype, and test. Data collection was carried out through observation and interviews with five teachers using the Madrasah Digital Report Card (RDM). The prototype was designed using Figma and tested for ease of use and system navigation. The results of the study indicate that the prototype design simplifies the grade management workflow and makes it easier for users to access system features. The integration of assessment features into a single interface page has the potential to improve system efficiency and user experience. Consequently, the design thinking method can be utilised as an effective approach in the design of the UI/UX for a web-based learning reporting system.